OPTIMALISASI PORTOFOLIO MENGGUNAKAN METODE MEAN-SEMIVARIANCE PADA SAHAM IDX30 - Tsara Firda Nabila; Sudarno sudarno; Masithoh Yessi Rochayani (Jurnal Gaussian, 2025)
Investment is one way to maximize income. Through investment, investors who invest funds will benefit. However, investment is inseparable from risk. Investors can reduce investment risk by forming an optimal portfolio. Mean-semivariance is one method of portfolio formation invented by Markowitz in 1959. Mean-semivariance is a mean-variance development method, but this method is free from all assumptions and this method measures portfolio risk by using semivariance and semideviation. The investment that many investors choose is a stock investment. This research uses stocks that have consistently joined the IDX30 for five years (2018-2022). IDX30 is composed of 30 stocks with relatively large market capitalization, high liquidity, and good fundamentals. The optimal portfolio is formed by calculating the weight of each stock using a function, so as to get the smallest risk. Based on the four optimal portfolios that are formed through the process, it is known that the optimal portfolio with the best performance is Portfolio 2. The Sharpe index belonging to Portfolio 2 is 0.083507. The investment weight for each share that makes up Portfolio 2 is 16.1039% for shares of PT Adaro Energy Indonesia Tbk; 57.5554% for shares of PT Indofood CBP Sukses Makmur Tbk; and 26.3407% for shares of PT Perusahaan Gas Negara Tbk.